Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Kompensasi Terhadap Loyalitas Karyawan (Studi Kasus PT Jawara Properti Indonesia) - Cahyono, Dwi Nur; Wahono, Budi; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research aims to determine and analyze leadership style, work environment and compensation on employee loyalty. The type of approach used is explanatory research. The sample used in this research used a saturated sample formula, with a total of 46 samples and used 14 statement indicators. The data analysis method used in this research is multiple linear regression analysis. The data testing used is simultaneous hypothesis testing (F test) and partial hypothesis testing (t test). The results of the research show that leadership style, work environment and compensation have a positive and significant influence simultaneously on employee loyalty at PT Jawara Properti Indonesia. Leadership style has a positive and significant effect on employee loyalty at PT Jawara Properti Indonesia. The work environment has a positive and significant effect on employee loyalty at PT Jawara Properti Indonesia. Compensation has a positive and significant effect on employee loyalty at PT Jawara Properti Indonesia. Keywords: Analyze Leadership Style, Work Environment, Compensation And Employee Loyalty.